Determination of the influence of interface delamination on the elastic properties of fiber reinforced composite materials - Borghei, Seyed Nima (2013)
The aim of this study was to investigate the influence of interface delamination on the elastic properties of fiber reinforced composite materials. Transverse Young’s modulus in the presence of different levels of localized and homogeneously distributed interface damage in two structures with 0.3 and 0.6 fiber volume fractions were simulated in a commercial finite element code. To achieve this, a new approach to simulate interface damage was addressed by selective merging of fiber and matrix nodes at the fiber-matrix interface. It was found that elastic properties were decreased by increasing interface delamination for both 0.3 and 0.6 fiber volume fractions. In addition, the 0.6 fiber volume fraction model showed higher elastic properties, but lower when the interface damage was increased to more than 45% due to the higher fraction of damaged fiber. Furthermore, localized damage results in slightly higher stiffness values than homogeneously distributed damage